Saudi Arabia in the new Middle East - Gause, F. Gregory (CSR (New York, N.Y.) ;, 2011)
The United States' relationship with Saudi Arabia has been one of the cornerstones of U.S. policy in the Middle East for decades. Despite their substantial differences in history, culture, and governance, the two countries have generally agreed on important political and economic issues and have often relied on each other to secure mutual aims. Their ongoing cooperation on maintaining regional stability, moderating the global oil market, and pursuing terrorists should not be downplayed. Yet for all the relationship's importance, it is increasingly imperiled by mistrust and misunderstanding. One major question is Saudi Arabia's stability. In this report, the author explores the foundations of Riyadh's present stability and potential sources of future unrest. It is difficult not to notice that Saudi Arabia avoided significant upheaval during the political uprisings that swept the Middle East in 2011, despite sharing many of the social and economic problems of Egypt, Yemen, and Libya. But unlike their counterparts in Cairo, Sanaa, and Tripoli, Riyadh's leadership was able to maintain order in large part by increasing public spending on housing and salaries, relying on loyal and well-equipped security forces, and utilizing its extensive patronage networks. The divisions within the political opposition also helped the government's cause. This is not to say that the stability of the House of Saud is assured. The author points out that the top heirs to the throne are elderly and the potential for disorderly squabbling may increase as a new generation enters the line of succession. Moreover, the population is growing quickly, and there is little reason to believe that oil will forever be able to buy social tranquility. Perhaps most important, the author argues, the leadership's response to the 2011 uprisings did little to forestall future crises; an opportunity for manageable political reform was mostly lost.